Some Remarks on the Jewish Life of Jesus (Toledot Yeshu) in Early Modern Europe Journal for Religion, Film and Media - Daniel Barbu (Journal for Religion, Film and Media, 2019)
The Jewish Life of Jesus (Toledot Yeshu) is perhaps one of the most infamous retellings of the gospel narrative of the pre-modern era. The present essay explores its reception and circulation of among both Jews and Christians in the period before and after the first editions of the work, by J.C. Wagenseil in 1681 and J.J. Huldreich in 1705. The work was an object of fascination for early modern scholars of Judaism and was regularly invoked in discussions concerned with the Talmud and other Jewish books alleged to be "blasphemous." For Jewish scholars, it was a source of embarrassment, although both the manuscript and documentary evidence demonstrates that many Jews did view Toledot Yeshu as a culturally significant narrative, worthy of being transmitted. It is here suggested that Toledot Yeshu, with its direct and emotional cogency, combining history, humour, and polemics, was indeed recognized by early-modern Jews and crypto-Jews as a powerful story, to which they could articulate their identity.